Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai pada Dinas Sosial Kota Surabaya - Kurniawati, Ria (Al Makki Publisher, 2025)
This study aims to analyze the influence of work environment and work motivation on employee performance at the Social Service Office of Surabaya City. A quantitative approach was employed using a survey method. The research sample consisted of 40 respondents who are active employees at the institution. Data were collected through questionnaires that had been tested for validity and reliability. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationships between variables through multiple linear regression analysis. The results indicate that the work environment has a positive and significant effect on employee performance. Likewise, work motivation also has a positive and significant effect on performance. These findings suggest that improving the quality of the work environment and enhancing employee motivation can significantly boost employee performance. This study provides important implications for the management of the Surabaya City Social Service in designing strategies to improve employee performance through workplace enhancement and motivation strengthening.